International economic law and governance : essays in honour of Mitsuo Matsushita - Matsushita, Mitsuo, 1933-; Chaisse, Julien; Lin, Caiyu (Oxford : Oxford University Press, 2017)
Celebrating the work of Mitsuo Matsuhita, this volume focuses on dispute resolution and the law and politics of the World Trade Organization, offering a critical and scholarly analysis of the current and future state of international economic governance.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 6, 2016).
Keywords: International economic relations -- Law and legislation; International law; Law; Laws of specific jurisdictions & specific areas of law